Exploring political ecology : Issues, problems, and solutions to the climate change crisis - Alexander, M. Ervin (New York : Routledge, 2025)
This book explores some of the conditions and underlying causes of the multiple environmental crises facing humanity. Rooted in anthropology, but multidisciplinary in scope, it surveys the many socio-cultural and socio-economic errors, foibles, and follies that brought us to these circumstances. Crucially and uniquely, it outlines an array of viable and practical solutions, some of which are radically different from the current status quo and cultural expectations. The first chapter canvasses the emerging, interdisciplinary field of political ecology, then Part I examines details and trends in agriculture. Part II portrays the threats posed by carbon dependent and combustive technologies as well as the hydro and nuclear energy systems now powering the majority of human actions in developed parts of the world and expanding beyond. The third part turns to consider solutions, including green new deals, de-growth policies, localization, agroecology, alternative energy systems, and many more possibilities. The conclusions engage with urgent moral and legal issues and outline social movement strategies$1 (Ball related to our collective neglect of climate change$1 (Band then finally speculate upon possible futures. This book is key reading for researchers and students interested in climate change across the social and physical sciences and humanities.s
Keywords: Environmental History